Microbial Community Dynamics and Metabolome Changes During Spontaneous Fermentation of Northeast Sauerkraut From Different Households - Yang, Xiaozhe; Hu, Wenzhong; Xiu, Zhilong; Jiang, Aili; Yang, Xiangyan; Saren, Gaowa; Ji, Yaru; Guan, Yuge; Feng, Ke (Frontiers in Microbiology, 2020)
Sauerkraut, one of the most popular traditional fermented vegetable foods in northern China, has been widely consumed for thousands of years. In this study, the physicochemical characteristics, microbial composition and succession, and metabolome profile were elucidated during the fermentation of traditional northeast sauerkraut sampled from different households. The microbial community structure as determined by high-throughoutput sequencing (HTS) technology demonstrated that Firmicutes and Proteobacteria were the predominant phyla and Weissella was the most abundant genus in all samples. Except for Weissella, higher abundance of Clostridium was observed in #1 sauerkraut, Clostridium and Enterobacter in #2 sauerkraut, and Lactobacillus in #3 sauerkraut, respectively. Meanwhile, Principal component analysis (PCA) revealed significant variances in the volatilome profile among different homemade sauerkraut. Acids and lactones were dominant in the #1 sauerkraut. The #2 sauerkraut had significantly higher contents of alcohols, aldehydes, esters, sulfides, and FAAs. In comparison, higher contents of terpenes and nitriles were found in the #3 sauerkraut. Furthermore, the potential correlations between the microbiota and volatilome profile were explored based on Spearman’s correlation analysis. Positive correlations were found between Clostridium, Enterobacter, Lactobacillus, Leuconostoc, Weissella and most volatile compounds. Pseudomonas, Chloroplast, Rhizobium, Aureimonas and Sphingomonas were negatively correlated with volatile compounds in sauerkraut. This study provided a comprehensive picture of the dynamics of microbiota and metabolites profile during the fermentation of different homemade northeast sauerkraut. The elucidation of correlation between microbiota and volatile compounds is helpful for guiding future improvement of the fermentation process and manufacturing high-quality sauerkraut.